The Use of Social Stories for Children with Pervasive Developmental Disorders - Banu Tortamış ÖZKAYA; Gökçe TEKİN (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
Children diagnosed with PDD (Pervasive Developmental Disorders) cannot effectively use the socialinteraction channels which significantly limit their participation in social life. The rapid increase in thenumber of children diagnosed with PDD led to the advancement and diversification of social skill interventionprograms. Social stories targeting to support the social development of children diagnosed with PDD wereexamined within a theoretical and applied framework in this study. Furthermore, recommendations weremade to introduce and implement social stories in the field of special education.